Impact of Proactive Personality and Career Adaptability on In-Role Performance through Job Crafting and Work Engagement in Indonesian Millennial Generation - Lidana Ega Nerissa; Riani Rachmawati (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This paper aims to examine whether proactive personality and career adaptability can predict work engagement and in-role performance through the utilization of job crafting behaviors, which have been analyzed using Partial Least Squares Structural Equation Modeling (PLS SEM). The study postulated that employees demonstrating proactive personality and career adaptability are more likely to actively shape their roles to enhance their engagement and performance. By integrating findings from prior research, an overarching model has been developed that can be utilized to cultivate work engagement and enhance in-role performance within contemporary workplaces. Data were collected from a sample of 180 millennial employees working in various organizations. The findings revealed that employees possessing proactive personality and career adaptability were most inclined to engage in job crafting, which in turn positively influenced their work engagement and performance. The majority of the results provided support for the hypothesized relationships. Job crafting was identified as a full mediator between career adaptability and work engagement, while the direct relationship between career adaptability and work engagement was not found to be statistically significant.